Non-motor Brain Regions in Non-dominant Hemisphere Are Influential in Decoding Movement Speed - Breault, Macauley Smith; Fitzgerald, Zachary B.; Sacré, Pierre; Gale, John T.; Sarma, Sridevi V.; González-Martínez, Jorge A. (Frontiers in Neuroscience, 2019)
Sensorimotor control studies have predominantly focused on how motor regions of the brain relay basic movement-related information such as position and velocity. However, motor control is often complex, involving the integration of sensory information, planning, visuomotor tracking, spatial mapping, retrieval and storage of memories, and may even be emotionally driven. This suggests that many more regions in the brain are involved beyond premotor and motor cortices. In this study, we exploited an experimental setup wherein activity from over 88 non-motor structures of the brain were recorded in eight human subjects executing a center-out motor task. The subjects were implanted with depth electrodes for clinical purposes. Using training data, we constructed subject-specific models that related movement speed to spectral power of neural activity in six different frequency bands as well as a combined model containing the aggregation of multiple frequency bands. We then tested the models by evaluating their ability to decode movement speed from neural activity in the test data set. The best models achieved a correlation of $0.38 ± 0.03$~(mean $±$ standard deviation) and mean squared error of $1.07 ± 0.09$. Further, the decoded speeds matched the categorical representation of the test trials as correct or incorrect with an accuracy of \SI{70±2.75}{\percent} across subjects. These models included features from regions such as the right hippocampus, middle temporal gyrus, intraparietal sulcus, and left fusiform gyrus across multiple frequency bands. Perhaps more interestingly, we observed that the non-dominant hemisphere (ipsilateral to dominant hand) was most influential in decoding movement speed.